Kepemimpinan pendidikan Islam: Konsep kepemimpinan pendidikan yang efektif - Ramadhani, Akhmad; Muttaqin, M. Imamul; Yunus, Jefrizal; Putri, Vina Karisma (Maliki Interdisciplinary Journal, 2024)
In the Regulation of the Minister of National Education Number 13 of 2007 concerning Standards for School/Madrasah Principals it has been established that there are five dimensions of competency, namely personality, managerial, entrepreneurial, supervision, and social. These five competencies must be inherent in the principal’s personality, so that he or she can become an effective leader. Within the School Based Management (SBM) framework, the school principal is responsible for implementing: 1) school management; 2) active, interactive, creative, effective and fun learning; and increasing community participation in supporting school programs. Therefore, school principals should have adequate managerial abilities. Apart from being a leader, the principal is also a manager, who is required to have managerial skills related to the realization of an effective school. Therefore, the position of principal cannot be held by just anyone. The principal must meet the minimum competition as previously mentioned.